ANALISIS PENERIMAAN DAN BAGI HASIL PAJAK KENDARAAN BERMOTOR PADA DINAS PENDAPATAN DAERAH PROVINSI SULAWESI UTARA - Theo, Jordi; Pangemanan, Sifrid; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2018)
Tax is one of the state and regional revenue that must be optimized to support the project in the framework of tourism. Motor Vehicle Tax is one type of Provincial Tax which will result from its receipt will also be submitted to Regency/City with profit sharing system. The results of the Motor Vehicle Tax Receipts shall be allocated at least 10% (percent percent) for the improvement of road infrastructure and improvements to public transportation modes. This study aims to determine and analyze Income from Motor Vehicle Tax at North Sulawesi Revenue Service Office. This research uses descriptive research method. The result of research shows that realization of profit sharing of motor vehicle tax in North Sulawesi province has been in accordance with Government Regulation and Distribution of Motorized Tax Realization in 2017 has exceeded predetermined target of provincial tax sector is high.Keywords: Taxes, Motor Vehicle Taxes, Profit Sharing